Customary Marine Tenure in Australia - Peterson, Nicolas; Rigsby, Bruce (Sydney University Press, 2014)
Most Australians are familiar with the concept of land ownership and understand the meaning of native title, which recognises Indigenous peoples' rights to land to which they are spiritually or culturally connected. The ownership of areas of the sea and its resources is often overlooked however, despite Aboriginal and Torres Strait Islander connections with the sea being just as important as those with the land. The papers in this volume demonstrate how the concept of customary marine tenure has developed in various communities and look at some of its implications. Originating in a session of papers at a conference in 1996, the papers in this volume were originally published as Oceania Monograph 48 in 1998.